The use of balloon dilation in revision sinus surgery. Issue 10 (29th May 2020) - Jang, David W.; Cyr, Derek D.; Schulz, Kristine; Scher, Richard; Ryan, Phil; Abi Hachem, Ralph; Witsell, David L.
Abstract : Background: Recent studies have demonstrated a dramatic increase in the use of balloon sinus dilation (BSD) in the United States. However, the use of BSD specifically in revision sinus surgery has not been investigated. This study addresses the question of how BSD is utilized as a tool in revision sinus surgery. Methods: Data from MarketScan (Truven Health) over a 5‐year period (2012‐2016) were analyzed. Patients who underwent a sinus procedure with a minimum of 2 years of follow‐up were included. Results: A total of 62, 304 patients met inclusion criteria; 6847 (10.99%) underwent revision. Age >55 years, the South geographical region, and medical comorbidities increased the odds of revision on multivariate analysis. For patients undergoing revision, BSD was used 11%, 21%, and 13% of the time for revisions of the maxillary, frontal, and sphenoid sinuses, respectively. For a sinus that underwent revision after an initial BSD, a repeat BSD was done close to 40% of the time. Conclusion: BSD is used frequently in the revision setting, especially for the frontal sinus and for patients who had already undergone an initial BSD. Our findings highlight the prevalent role of BSD in revision surgery and the need to evaluate such practices.